Nano-catalyst based on clay confinement controllable reconstruction as well as preparation method and application of nano-catalyst

During the electrocatalytic N2O reduction process, metallic eleroite composite catalyst is prepared using eleroite and metal precursors, and in-situ electrochemical reconstruction is carried out, the problem of uncontrollable reconstruction of copper-based catalysts is solved, and the N2O reduction reaction is achieved with a simple process and low cost.

CN119685872AActive Publication Date: 2025-03-25CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510000835.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-25
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the prior art, uncontrollable reconstruction of copper-based catalysts often occurs during electrocatalytic N2O reduction, resulting in low reactive activity and product selectivity, complex process and high cost.

Method used

By mixing elerosite, metal precursor, ascorbic acid and water, a metallic elerosite composite catalyst was prepared, and in-situ electrochemical reconstruction was performed on carbon paper to prepare a nanocatalyst based on clay domain-controllable reconstruction.

Benefits of technology

Controllable reconstruction of copper-based catalysts is realized, and the activity and selectivity of electrocatalytic N2O reduction reactions are improved. The process is simple, the conditions are mild, the energy consumption is low and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685872A_ABST
    Figure CN119685872A_ABST
Patent Text Reader

Abstract

The invention provides a nano-catalyst based on clay confinement controllable reconstruction and a preparation method and application thereof, and relates to the field of electrochemistry. The preparation method comprises the following steps: mixing halloysite, a metal precursor, ascorbic acid and water, stirring, carrying out solid-liquid separation, and carrying out first drying to obtain mixed powder; heating the mixed powder in a reducing atmosphere to obtain a metal-based halloysite composite catalyst; mixing with a Nafion / ethanol mixed solution, and dispersing to obtain an ink solution; adding the ink solution to carbon paper with a gas diffusion layer, and performing secondary drying to obtain a pre-catalyst; and carrying out a catalytic N2O reduction reaction on the pre-catalyst to obtain the nano-catalyst based on clay confinement controllable reconstruction. The nano-catalyst based on clay confinement controllable reconstruction provided by the invention can electrocatalyze N2O to be reduced into N2, the Faraday efficiency can reach 96%, and the preparation method is simple in process, low in cost and low in energy consumption, and can be widely applied to electrochemical reduction of greenhouse gases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to a nanocatalyst based on clay confinement and controllable reconstruction, and a preparation method and use thereof. Background Art

[0002] N2O is one of the main greenhouse gases, and its greenhouse effect is nearly 300 times that of CO2. Using renewable energy to harmlessly treat N2O and convert it into N2 has become a hot topic of concern. Among them, N2O electrochemical reduction (N2ORR) has the advantages of mild reaction conditions, high efficiency, economy, and environmental protection. It is a very promising energy conversion technology that can achieve harmless treatment and zero emissions of greenhouse gases. However, since the conversion efficiency of N2ORR is limited by slow kinetics and is often accompanied by severe hydrogen evolution side reactions, the reaction activity and product selectivity are low. Therefore, it is urgent to develop new N2ORR catalysts with high selectivity, high conversion efficiency, and low cost.

[0003] In the electrocatalytic system, the electrocatalyst is the most important part. Copper-based catalysts have shown great potential in electrocatalytic N2O, but during the electrocatalytic process, copper-based catalysts often undergo uncontrollable reconstruction, which reduces the activity of the reaction. At present, in order to solve the reconstruction problem of copper-based catalysts, other confined materials are often used, such as carbon materials such as graphene, to confine them, and then regulate the electrocatalytic reconstruction process of copper-based catalysts under different atmosphere conditions. Natural clay minerals have layered and tubular confined spaces and are natural microreactors. The confined spaces of clay minerals can effectively reconstruct copper in a controllable manner to prepare evenly dispersed copper-based clay mineral catalysts, thereby enhancing electrocatalytic activity.

[0004] Patent CN116536694A discloses a method for synthesizing a nickel single-atom catalyst based on electrochemical reconstruction of a metal organic framework and its application in electrocatalytic CO2 reduction. Ni-MOF-74 is reconstructed in situ to synthesize a nickel single-atom catalyst in electrocatalytic CO2 reduction, and CO2 is reduced to CO. However, the reconstruction method is complex and costly, and the catalytic scenario is applied to CO2, and less work is done on electrocatalytic N2O reduction.

[0005] How to develop a new type of high-efficiency catalyst for electrocatalytic N2O reduction that meets the requirements of simple process flow, high catalytic reaction activity and low cost is a technical problem that needs to be solved at present. Summary of the invention

[0006] The purpose of this application is to provide a nanocatalyst based on clay confinement and controllable reconstruction, and a preparation method and use thereof, in order to solve the above-mentioned problems.

[0007] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a nanocatalyst based on clay confinement and controllable reconstruction, comprising: Mixing halloysite, a metal precursor, ascorbic acid and water to obtain a mixed solution, evacuating the mixed solution, breaking the vacuum, stirring the mixed solution, separating the solid from the liquid, and first drying the mixed solution to obtain a mixed powder; heating the mixed powder under a reducing atmosphere to obtain a metal-based halloysite composite catalyst; The metal-based halloysite composite catalyst is mixed with a Nafion / ethanol mixed solution to disperse and obtain an ink solution; Adding the ink solution to the carbon paper with the gas diffusion layer, and performing a second drying to obtain a pre-catalyst; The precatalyst is subjected to an electrocatalytic N2O reduction reaction to obtain the nanocatalyst based on clay confinement and controllable reconstruction.

[0008] Halloysite has a hollow structure, which provides a basis for the confined and controllable reconstruction of metals; ascorbic acid not only provides a carbon source but also can initially reduce metal precursors.

[0009] Compared with pre-catalysts, nanocatalysts based on clay confinement and controllable reconstruction have obvious catalytic efficiency advantages.

[0010] The purpose of mixing with the Nafion / ethanol mixed solution is to better load the metal-based halloysite composite catalyst on the carbon paper, and the carbon paper is used as a current collector.

[0011] The precatalyst undergoes in-situ electrochemical reconstruction under constant voltage to generate copper nanoparticles, and the electrocatalytic reduction product of N2O is N2. After the final catalyst is obtained, the catalyst is still used for the electrocatalytic N2O reduction reaction.

[0012] Preferably, the metal precursor includes compounds corresponding to one or more elements selected from the group consisting of copper, iron, cobalt, nickel and gold.

[0013] Preferably, the method for preparing the nanocatalyst based on clay confinement controllable reconstruction meets one or more of the following conditions: (1) The mass ratio of the halloysite, the metal precursor, and the ascorbic acid is (0.05-0.5): (0.01-0.15): (0.3-3); (2) The ratio of the volume of the water to the total mass of the halloysite, the metal precursor, and the ascorbic acid is 50 mL: (0.36-3.65) g; (3) The stirring time is 12-24 h; (4) The first drying temperature is 50-80°C and the time is 6-18 hours; (5) The vacuuming comprises: placing the mixed solution in a vacuum drying oven and evacuating the mixture to -0.1 MPa for 10-30 min, repeating this process three times.

[0014] Preferably, the maximum heating temperature is 550-950°C, the heating rate is 2-10°C / min, and the heating time is 1-4 h; The reducing atmosphere is a hydrogen-argon mixed atmosphere, with the volume proportion of hydrogen being 2-10%.

[0015] Preferably, in the Nafion / ethanol mixed solution, the volume ratio of Nafion to ethanol is 1:20 to 1:100.

[0016] Preferably, the method for preparing the nanocatalyst based on clay confinement controllable reconstruction meets one or more of the following conditions: (1) In the ink solution, the mass volume ratio of the metal-based halloysite composite catalyst to the Nafion / ethanol mixed solution is 10 mg: 2 mL to 50 mg: 2 mL; (2) The dispersion is carried out by ultrasonication for 20-60 min; (3) The size of the carbon paper is 2 cm×2 cm~5 cm×5 cm; (4) The adding method is dropwise addition, and the dropwise addition amount is 800-2000 μL; (5) The temperature of the second drying is 50-80°C.

[0017] Preferably, the voltage of the electrocatalytic N2O reduction reaction is -0.2~1.4 V.

[0018] The present application also provides a nanocatalyst based on clay confinement and controllable reconstruction, which is prepared using the preparation method of the nanocatalyst based on clay confinement and controllable reconstruction. The present application also provides a use of the nanocatalyst based on clay confinement and controllable reconstruction, which is used as a catalyst for N2O reduction reaction.

[0019] Preferably, the N2O reduction reaction comprises: A three-electrode system is used for electrocatalytic N2O reduction, in which the reference electrode is a saturated Ag / AgCl electrode, the counter electrode is a Ni mesh, and the working electrode is the nanocatalyst based on clay confinement controllable reconstruction; the cathode and anode electrolytes are 0.1-1 MKOH solution, or 0.1 M NaOH +0.9 M NaClO4, pH=12.7 solution, and the anode and cathode chambers are separated by a Fumasep FAA-3-50 membrane, or 0.5 M HClO4+1 M NaClO4, pH=0.5 solution is used as the electrolyte, and the anode and cathode chambers are separated by a Nafion 117 membrane, and the electrolytic cell type used is a flow cell.

[0020] Compared with the prior art, the beneficial effects of this application include: The preparation method of nanocatalyst based on controllable reconstruction of clay confinement provided in the present application is simple in method for synthesizing metal-based nanocatalysts under mild conditions. The metal / HNT / C catalyst is drop-coated on carbon paper containing a gas diffusion layer, and the nanocatalyst is synthesized (electrocatalytic N2O reduction reaction) by in-situ reconstruction using constant voltage. The process is simple and easy to operate, can be completed at room temperature, has low energy consumption and is safe.

[0021] The nanocatalyst based on clay confinement and controllable reconstruction provided in the present application has good N2ORR performance and can generate N2 with high activity and high selectivity. At -0.2~1.4 V (relative to the reversible hydrogen electrode), the Faradaic efficiency (FE) of N2 can reach more than 90%, and the highest can reach 96.3%, which is better than most existing N2ORR nanocatalysts.

[0022] The synthesis method and catalytic method provided in the present application have simple process, high catalytic efficiency and low cost, and provide a new idea for the synthesis and application of transition metal nanocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0024] Figure 1 is the X-ray diffraction pattern of the Cu / HNT / C precatalyst prepared in Example 1; Figure 2 This is a transmission electron microscopy image of the Cu / HNT / C precatalyst prepared in Example 1; Figure 3 This is the energy spectrum of the Cu / HNT / C precatalyst prepared in Example 1; Figure 4The linear voltammetric scan curve (LSV) of the Cu / HNT / C precatalyst prepared in Example 1; Figure 5 The electrochemically active specific surface area of ​​the Cu / HNT / C precatalyst prepared in Example 1 and the commercial Cu nanoparticles; Figure 6 The impedance spectrum (EIS) of the Cu / HNT / C catalyst prepared in Example 1 before and after the electrocatalytic N2O reaction; Figure 7 The linear voltammetric scanning curve of the Cu / HNT / C catalyst prepared in Example 1 under different atmospheres; Figure 8 This is a Faraday efficiency diagram of N2 obtained by electrocatalytic reduction of N2O using the Cu / HNT / C catalyst prepared in Example 1; Fig. 9 This is a stability test diagram of the Cu / HNT / C catalyst prepared in Example 1; Fig.10 Comparison of the reconstructed transmission electron microscopy images of the Cu / HNT / C catalyst prepared in Example 1 and the commercial Cu nanoparticles during the electrocatalytic N2O reduction process; Fig.11 The Auger electron spectra of the Cu / HNT / C catalyst prepared in Example 1 under different conditions; Fig.12 This is the isotope mass spectrum of the electrocatalytic N2O reduction product of the Cu / HNT / C catalyst prepared in Example 1; Fig.13 The Gibbs free energy diagram of the N2O reduction reaction path in the Cu / HNT / C catalyst prepared in Example 1; Fig.14 Linear voltammetric scan curves of the Cu / HNT / C catalyst prepared in Example 2 in different electrolytes; Fig.15 This is the linear voltammetric scan curve of the Cu / HNT / C catalyst prepared in Example 3. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] Example 1 This embodiment provides a nanocatalyst based on clay confinement and controllable reconstruction, and the preparation method thereof is as follows: Step 1: At room temperature, halloysite, copper chloride and ascorbic acid were stirred in 50 mL of deionized water at a mass ratio of 0.05 g: 0.08 g: 2 g, and the mixed solution was placed in a vacuum drying oven and evacuated to -0.1 MPa for 30 min. After repeating 3 times, it was stirred for 12 h to further mix the mixture, and then the mixed solution was filtered, and after solid-liquid separation, the mixed solid powder was placed in an oven and dried at 60°C for 12 h. The obtained mixed powder was placed in a tubular furnace, and the temperature was raised to 550°C at a rate of 5°C / min and maintained for 2 h in a 5% H2-Ar atmosphere to obtain a Cu / HNT / C precatalyst.

[0027] Step 2: At room temperature, weigh 10 mg of Cu / HNT / C precatalyst and dissolve it in 2 mL of Nafion ethanol mixed solution (volume ratio of 1:20). After ultrasonication for 30 min, mix well and drop-coat it on a 2 cm*2 cm carbon paper with a gas diffusion layer at a rate of 100 μL / time. Dry it at 60 °C to make the catalyst loading amount 1 mg cm -2 .

[0028] Step 3: A three-electrode system was used for in-situ electrochemical reconstruction and electrocatalytic N2O reduction. The reference electrode was a saturated Ag / AgCl electrode, the counter electrode was a Ni mesh, and the working electrode was the carbon paper loaded with Cu / HNT / C precatalyst prepared in step 2. The cathode and anode electrolytes were both 1 M KOH, and the anode and cathode chambers were separated by a Fumasep FAA-3-50 membrane. The nano Cu / HNT / C catalyst was reconstructed in situ under a certain voltage (-0.2~-1.4 V relative to the reversible standard hydrogen electrode) and directly used for electrocatalytic N2O reduction. The obtained product was analyzed by gas chromatography.

[0029] The precatalyst obtained in step 1 of Example 1 was subjected to an X-ray diffraction test (XRD). Figure 1 As shown; and the precatalyst was analyzed by transmission electron microscopy (HRTEM), as shown Figure 2 As shown; the pre-catalyst was subjected to energy spectrum analysis, and the results were as follows Figure 3 As shown. Figure 1 It can be seen that the Cu / HNT / C composite material was prepared. Figure 2 It can be seen that Cu is successfully loaded inside the HNT tube. Figure 3 The element distribution of the Cu / HNT / C composite material (precatalyst) can be obtained.

[0030] Example 2 The steps of Example 1 were repeated, except that the cathode electrolytes in Example 1 were changed to 0.5 M HClO4 + 1 M NaClO4 (pH = 0.5) and 0.1 M NaOH + 0.9 M NaClO4 (pH = 12.7). The prepared Cu / HNT / C catalyst was used for electrocatalytic N2O reduction.

[0031] The performance of the electrocatalytic system used in Example 2 is as follows Fig.14 As shown, from Fig.14 It can be seen that with the increase of electrolyte pH, its electrocatalytic activity increases, indicating that the catalyst is more suitable for N2O reduction under alkaline conditions.

[0032] Example 3 The operating steps of Example 1 were repeated, except that the initial addition amount of CuCl2, the calcination time and the initial addition amount of ascorbic acid in step 1 of Example 1 were changed. Fig.15 The linear voltammetric curves of the Cu / HNT / C catalysts prepared with different initial addition amounts of CuCl2, calcination time and initial addition amounts of ascorbic acid all have good N2ORR performance.

[0033] Comparative Example 1 Commercial Cu nanoparticles were used as a control (nano Cu). Different from Example 1, in the process of testing N2O reduction, the catalyst supported on the carbon paper was commercial Cu nanoparticles, such as Figure 4 As shown in (black curve), at the same voltage, its current density is not as high as that in Example 1, indicating that its activity is not as high as that of the Cu / HNT / C catalyst.

[0034] Comparative Example 2 The difference from Example 1 is that no ascorbic acid is added during the preparation process, halloysite is replaced by carbon nanotubes, and the other conditions remain unchanged. Figure 4 As shown in (red curve), at the same voltage, its current density is not as high as that in Example 1, indicating that its activity is not as high as that of the Cu / HNT / C catalyst.

[0035] Comparative Example 3 The difference from Example 1 is that copper chloride is not added during the preparation process, and the other conditions remain unchanged. Figure 4 As shown in the green curve, under the same voltage, its current density is not as high as that in Example 1, indicating that its activity is not as high as that of the Cu / HNT / C catalyst. In particular, its current density is the lowest among the comparative examples, indicating that Cu is the active center of the reaction and Cu is an indispensable catalytic raw material.

[0036] Comparative Example 4 The difference from Example 1 is that no ascorbic acid is added during the preparation process, and the other conditions remain unchanged. Figure 4 As shown in the purple curve, under the same voltage, its current density is not as high as that in Example 1, indicating that its activity is not as high as that of the Cu / HNT / C catalyst. Among them, ascorbic acid serves as a C source, and HNT itself is not conductive and has no C coating, which further affects the activity of the reaction.

[0037] Comparative Example 5 The difference from Example 1 is that during the preparation process, ascorbic acid is replaced by glucose, and the other parts remain unchanged. Figure 4 As shown in (orange curve), under the same voltage, its current density is not as high as that in Example 1, indicating that its activity is not as high as that of the Cu / HNT / C catalyst. The comparison shows that ascorbic acid is more effective as a C source, which may be related to the strong reducing property of ascorbic acid. While providing a C source, ascorbic acid can further reduce the CuCl2 in the system.

[0038] Figure 4 The linear voltammetric scanning curve (LSV) and the corresponding Tafel slope of the final nano Cu / HNT / C catalyst (blue curve) prepared in Example 1 are compared with other catalysts with different compositions (catalysts of comparative examples). It can be seen from the figure that the electrochemical activity of the Cu / HNT / C catalyst is better than that of catalysts with other compositions. Figure 5 Figure 3 is the electrochemically active specific surface area (ECSA) of nano Cu / HNT / C catalyst and commercial Cu nanoparticles, where (a) is the CV curve of commercial Cu nanoparticles at different scanning speeds, and (b) is the CV curve of Cu / HNT / C catalyst at different scanning speeds. The slopes of the electrochemically active specific surface areas are calculated based on (a) and (b). In (c), the blue curve slope represents the ECSA of the Cu / HNT / C catalyst, and the red curve slope represents the ECSA of commercial Cu nanoparticles. The slope of the Cu / HNT / C catalyst is greater than that of the Cu nanoparticles, indicating that the nano Cu / HNT / C catalyst has more reaction active sites. Figure 6 Impedance diagrams of the pre-catalyst and the final nano-Cu / HNT / C catalyst (before and after electrocatalytic reaction). It can be inferred that the charge transfer efficiency of the final nano-Cu / HNT / C catalyst is higher than that of the pre-catalyst.

[0039] Figure 7 The linear voltammetric scanning curve of the final nano Cu / HNT / C catalyst prepared in Example 1 of the present application under different atmospheres; Figure 8 This is a Faraday efficiency diagram of N2 obtained by electrocatalytic reduction of N2O using the final nano Cu / HNT / C catalyst prepared in Example 1 of the present application; Fig. 9 This is a stability test diagram of the final nano Cu / HNT / C catalyst prepared in Example 1 of this application. Figure 7It can be seen that the final nano Cu / HNT / C catalyst has higher activity under N2O. Figure 8 It can be seen that the final nano Cu / HNT / C catalyst prepared can maintain a product selectivity of more than 90% in the voltage range of -0.2~-1.4 V (relative to the reversible hydrogen electrode). And the nano Cu / HNT / C catalyst prepared at -0.6 V (relative to the reversible hydrogen electrode) has a maximum N2 Faraday efficiency of 96.3% for electrocatalytic N2O reduction. The nano Cu / HNT / C catalyst prepared at -0.1 V (relative to the reversible hydrogen electrode) in Example 1 was tested for stability, and the results are as follows Fig. 9 As shown. Fig. 9 It can be seen that the synthesized nano Cu / HNT / C catalyst has good stability and can operate stably for more than 12 h, indicating that it has good electrocatalytic N2O reduction performance and has the prospect of being put into industrial use.

[0040] Fig.10 The final nano Cu / HNT / C catalyst obtained in Example 1 and the reconstructed transmission electron microscopy (TEM) of commercial Cu nanoparticles during the electrocatalytic N2O reduction process are shown in the figure. It can be seen from the figure that the commercial Cu nanoparticles undergo a process of first agglomerating into large particles during the electrocatalytic N2O reduction process, and reconstruct some nano Cu particles with a diameter of less than 10 nm at the edge of the particles. During the electrocatalytic N2O reduction process of the Cu / HNT / C catalyst, the Cu in the HNT tube gradually diffuses to the tube mouth and gradually disperses evenly on the outer surface of the HNT, thereby obtaining a nano Cu / HNT / C catalyst with evenly dispersed Cu particles less than 10 nm. Fig.11 This is the fine spectrum of the Auger electron spectrum of Cu, from Fig.11 It can be seen that after the reaction, the surface valence state of the Cu / HNT / C catalyst synthesized in Example 1 is further reduced to 0 valence.

[0041] Fig.12 and Fig.13 The mechanism diagram of electrocatalytic N2O reduction of the nano Cu / HNT / C catalyst prepared in Example 1. Fig.12 This is the isotope mass spectrum of the electrocatalytic N2O reduction products of the nano Cu / HNT / C catalyst. It can be seen from the figure that in the N2 product of the electrocatalytic N2O reduction, 15 The N labeling percentage is 63.51%, indicating that most of the N2 reduced by N2O comes from the reaction raw material N2O. Fig.13 is the Gibbs free energy of the N2ORR reaction pathway in the nano Cu / HNT / C catalyst, according to Fig.13It can be seen that the N-terminal adsorption configuration is easier to interact with Cu than the O-terminal adsorption configuration, thereby forming a Cu-N bond. During the N-terminal adsorption process, N2O dissociates at the Cu / C site to further form N2.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a nanocatalyst based on clay confinement and controllable reconstruction, characterized in that: include: Halloysite, a metal precursor, ascorbic acid and water are mixed to obtain a mixed solution, the mixed solution is evacuated and then broken, stirred, solid-liquid separated, and first dried to obtain a mixed powder; heating the mixed powder under a reducing atmosphere to obtain a metal-based halloysite composite catalyst; The metal-based halloysite composite catalyst is mixed with a Nafion / ethanol mixed solution to disperse and obtain an ink solution; Adding the ink solution to the carbon paper with the gas diffusion layer, and performing a second drying to obtain a pre-catalyst; The precatalyst is subjected to an electrocatalytic N2O reduction reaction to obtain the nanocatalyst based on clay confinement and controllable reconstruction.

2. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to claim 1, characterized in that: The metal precursor includes compounds corresponding to one or more elements of copper, iron, cobalt, nickel, and gold; Copper chloride is preferred.

3. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to claim 1, characterized in that: One or more of the following conditions are met: (1) The mass ratio of the halloysite, the metal precursor, and the ascorbic acid is (0.05-0.5): (0.01-0.15): (0.3-3); (2) The ratio of the volume of the water to the total mass of the halloysite, the metal precursor, and the ascorbic acid is 50 mL: (0.36-3.65) g; (3) The stirring time is 12-24 h; (4) The first drying temperature is 50-80°C and the time is 6-18 hours (5) The vacuuming comprises: placing the mixed solution in a vacuum drying oven and evacuating the mixture to -0.1 MPa for 10-30 min, repeating this process three times.

4. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to claim 1, characterized in that: The maximum heating temperature is 550-950°C, the heating rate is 2-10°C / min, and the heating time is 1-4 h; The reducing atmosphere is a hydrogen-argon mixed atmosphere, with the volume proportion of hydrogen being 2-10%.

5. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to claim 1, characterized in that: In the Nafion / ethanol mixed solution, the volume ratio of Nafion to ethanol is 1:20-1:

100.

6. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to claim 1, characterized in that: One or more of the following conditions are met: (1) In the ink solution, the mass volume ratio of the metal-based halloysite composite catalyst to the Nafion / ethanol mixed solution is 10 mg: 2 mL to 50 mg: 2 mL; (2) The dispersion is carried out by ultrasonication for 20-60 min; (3) The size of the carbon paper is 2 cm×2 cm~5 cm×5 cm; (4) The adding method is dropwise addition, and the dropwise addition amount is 800-2000 μL; (5) The temperature of the second drying is 50-80°C.

7. The method for preparing a nanocatalyst based on clay confinement and controllable reconstruction according to any one of claims 1 to 6, characterized in that: The voltage of the electrocatalytic N2O reduction reaction is -0.2~1.4 V.

8. A nanocatalyst based on clay confinement and controllable reconstruction, characterized in that: The nanocatalyst is prepared by the method for preparing the nanocatalyst based on clay confinement and controllable reconstruction as described in any one of claims 1 to 7.

9. A use of the nanocatalyst based on clay confinement and controllable reconstruction according to claim 8, characterized in that: Used as a catalyst for N2O reduction reaction.

10. The use of the nanocatalyst based on clay confinement controllable reconstruction according to claim 9, characterized in that: The N2O reduction reaction comprises: A three-electrode system is used for electrocatalytic N2O reduction, in which the reference electrode is a saturated Ag / AgCl electrode, the counter electrode is a Ni mesh, and the working electrode is the nanocatalyst based on clay confinement controllable reconstruction; the cathode and anode electrolytes are 0.1-1 M KOH solution, or 0.1 M NaOH +0.9 M NaClO4, pH=12.7 solution as the electrolyte, and the anode and cathode chambers are separated by a Fumasep FAA-3-50 membrane, or 0.5 M HClO4+1 M NaClO4, pH=0.5 solution as the electrolyte, and the anode and cathode chambers are separated by a Nafion117 membrane, and the electrolytic cell type used is a flow cell.

Citation Information

Patent Citations

  • Halloysite-loaded nickel-based nano-catalyst as well as preparation method and application thereof

    CN115532265A

  • Monatomic catalyst based on metal organic framework electrochemical reconstruction as well as synthesis method and application of monatomic catalyst

    CN116536694A

  • Carbon nitride modified halloysite supported nano-metal composite catalyst as well as preparation method and application thereof

    CN117884162A

  • Halloysite-based nanocomposites and methods of making and using the same

    US20210016250A1

  • Nano-palladium alloy catalyst for electrocatalytic reduction of co 2, and preparation method therefor and use thereof

    WO2023174049A1